Asymmetric Organocatalysis and the Nitro Group Functionality - Aitken, Lewis S.; Arezki, Natasha R.; Dell’Isola, Antonio; Cobb, Alexander J. A. (Synthesis, 2013)
The nitro group is an exceptionally versatile functional group, not only because it is essentially a masked amine, but also because its chemistry can be exploited in a number of useful ways. Asymmetric organocatalysis in particular has capitalized on the use of the nitro group towards the synthesis of a variety of nitrogen-containing targets. Perhaps of greatest interest is that this functional group has been shown to be invaluable within the rapidly expanding field of organocatalytic domino reactions. This review features selected examples of nitro group reactivity in organocatalysis to demonstrate its dynamism and utility.1 Introduction2 Nitroalkanes in Organocatalysis2.1 Secondary Amine Catalyzed Nitronate Reactions2.2 Brønsted Acid Catalyzed Nitronate Reactions2.3 Phase-Transfer-Catalyzed Nitronate Reactions3 Conjugated Nitro Compounds in Organocatalysis3.1 Secondary Amine Catalyzed Reactions with Conjugated Nitro Compounds3.2 Brønsted Acid Catalyzed Conjugate Additions to Nitroolefins3.3 Phase-Transfer-Catalyzed Conjugate Additions to Nitroolefins4 Domino Processes in Organocatalysis Using Nitroolefins4.1 Secondary Amine Catalyzed Domino Processes4.2 Brønsted Acid Catalyzed Domino Processes5 Conclusions
Keywords: organocatalysis; nitro group; conjugate addition; nucleophilic addition; cyclization; cascade reaction; domino reaction